AN EXPERIMENTAL AND THEORETICAL DETERMINATION OF OXYGEN ISOTOPE FRACTIONATION IN THE SYSTEM MAGNETITE-H2O FROM 300 TO 800°C - Cole D.R.; Horita J.; Polyakov V.B.; Valley J.W.; Spicuzza M.J.; Coffey D.W. (My University, 2004)
Oxygen isotope fractionations have been determined between magnetite and water from 300 to 800°C and pressures between 10 and 215MPa. We selected three reaction pathways to investigate fractionation: (a) reaction of fine-grained magnetite with dilute aqueous NaCl solutions; (b) reduction of fine-grained hematite through reaction with dilute acetic acid; and (c) oxidation of fine iron power in either pure water or dilute NaCl solutions. Effective use of acetic acid was limited to temperatures up to about 400°C, whereas oxide-solution isotope exchange experiments were conducted at all temperatures. Equilibrium 18O/16O fractionation factors were calculated from the oxide-water experiments by means of the partial isotope exchange method, where generally four isotopically different waters were used at any given temperature. Each run product was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and on a limited basis, high-resolution transmission electron microscopy (HRTEM) and Mössbauer spectroscopy. Results from the microscopic examinations indicate the formation of well-crystallized octahedra and dodecahedra of magnetite where the extent of crystallization, grain size, and grain habit depend on the initial starting material, P, T, solution composition, and duration of the run.